From a post-traumatic culture toward the cultural trauma of post-9/11 - Jabarouti, Roya; Mani, ManiMangai (Australian International Academic Centre, 2014)
Over the past decade, the impact of the terroristic attacks of September 11, 2001 on American culture has been the prominent subject of various discussions. This has led to a large body of theoretical and experimental works known as ‘post-9/11’, which provides evidence for what Smelser’s believes to be the cultural trauma of 9/11. This study sets out to present a review of post 9/11 literature, with the perspective of cultural trauma as suggested by Neil J. Smelser, to provide a comprehensive understanding of this collective experience. This analysis highlights the role of the historical background and socio-cultural context in the establishment of cultural trauma. It also indicates the social agents and cultural elements that contributed to the embeddedness and spread of this phenomenon among the Americans. Finally, it indicates the most prominent collective response of the Americans, and as its consequences.